2019
DOI: 10.7150/jca.35898
|View full text |Cite
|
Sign up to set email alerts
|

EBUS-TNBA 22G samples: Comparison of PD-L1 expression between DAKO and BIOCARE®

Abstract: Introduction: Lung cancer is diagnosed at advanced stage due to lack of early disease symptoms. Currently we have several different biopsy techniques such as; radial endobronchial ultrasound, convex probe endobronchial ultrasound, electromagnetic navigation, ct guided biospy and transthoracic ultrasound biopsy. Novel therapies such as; immunotherapy is being used for non-small cell lung cancer in the everyday clinical practice as first and second line treatment. Programmed ligand-1 is essential in order to adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Endobronchial ultrasound with convex probe and PET-CT combined provide in several lung cancer cases the staging of the disease. In advanced stage disease molecular biomarkers such epidermal growth factor (EGFR), anaplastic lymphoma kinase (ALK), proto-oncogene B-Raf (BRAF), proto-oncogene tyrosine-protein kinase (ROS1) and programmed death-ligand 1 (PD-L1), provide us with useful information regarding the treatment of the patient 8 - 11 . PD-L1 can be efficiently assessed with cell-blocks 11 - 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Endobronchial ultrasound with convex probe and PET-CT combined provide in several lung cancer cases the staging of the disease. In advanced stage disease molecular biomarkers such epidermal growth factor (EGFR), anaplastic lymphoma kinase (ALK), proto-oncogene B-Raf (BRAF), proto-oncogene tyrosine-protein kinase (ROS1) and programmed death-ligand 1 (PD-L1), provide us with useful information regarding the treatment of the patient 8 - 11 . PD-L1 can be efficiently assessed with cell-blocks 11 - 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover; the issue method of administration, should be easy for the patient and without complication. EBUS-TBNA is a safe method under mild anesthesia and with small needles that do not cause any serious adverse effects 4 , 5 , 40 , 41 . We had to carefully choose which patients would benefit from this treatment modality and these patients would be two groups with endobronchial lesions and large parenchymal masses.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of complications after EBUS-TBNA has been reported to be 0.15% to 0.46% 18,19 , and EchoTip ProCore® was safe as it did not increase the incidence of complications. Furthermore, several studies have reported that samples obtained using EBUS-TBNA as a cell block can allow PD-L1 staining 20,21 . The present study shows that EBUS-TBNA with EchoTip ProCore® can consistently yield large tissues suitable for direct immunostaining of PD-L1 (Figure 3).…”
Section: Discussionmentioning
confidence: 99%